Modulating the Enantiodiscrimination Features of Inherently Chiral Selectors by Molecular Design: A HPLC and Voltammetry Study Case with Atropisomeric 2, 2'‐Biindole‐Based Monomers and Oligomer Films. Issue 52 (12th August 2021) - Scapinello, Luca; Grecchi, Sara; Rossi, Sergio; Arduini, Fabiana; Arnaboldi, Serena; Penoni, Andrea; Cirilli, Roberto; Romana Mussini, Patrizia; Benincori, Tiziana
Abstract: A family of inherently chiral electroactive selectors based on the 2, 2'‐biindole atropisomeric scaffold, of easy synthesis and modulable functional properties, is studied in cascade in two enantioselection contexts. They are at first investigated as probes in enantioselective HPLC, studying molecular structure and temperature effects, and achieving very efficient semipreparative enantioseparation. The enantiomers thus obtained, of remarkable chiroptical features (optical rotation as well as circular dichroism), are successfully applied as selectors in chiral voltammetry in different media for discrimination of the enantiomers of chiral electroactive probes, either by conversion into enantiopure electroactive electrode surfaces by electrooligomerization on glassy carbon substrate (the two monomers with shorter alkyl chains), or as chiral additive in achiral ionic liquid (the monomer with longest alkyl chains). Discrimination is conveniently and reproducibly achieved in terms of significant potential differences for the two enantiomers, specularly inverting either probe or selector configuration. In one case successful discrimination is also observed with the two probe enantiomers concurrently present, either as racemate or with enantiomeric excesses, neatly accounted for by the peak current ratios. Abstract : A series of inherently chiral electroactive selectors based on the 2, 2'‐biindole atropisomeric scaffold is studied in two enantiodiscrimination contests: as probes in enantioselective HPLC and as selectors in chiral voltammetry for successful discrimination of the enantiomers of chiral electroactive probes, either by conversion into enantiopure electroactive electrode surfaces or as chiral additive in achiral ionic liquid.